The possibility to combine longitudinal and cross-sectional design for studying development - Ignatavičienė, Kristina; Žukauskienė, Rita (Psichologija, 2002)
The fact that the time dimension is included in a prospective, longitudinal study gives it its unique value for studying development. However, it also implies some problems for research, such as cohort effects and some others. Therefore, it could be very valuable to combine the longitudinal design with cross-sectional design. The aim of current study is to illustrate the possibility to combine these research designs in order to assess the developmental features of emotional and behavioural problems in childhood. Data from longitudinal study collected in 1997, 1999, and 2001 when children were 9-12 years of age (n = 853) is used for this analysis. The longitudinal and cross-sectional analysis of data revealed the fact that over the time the mean level of emotional and behavioural problems for 9-10 year old children remain similar, when mean level of emotional and behavioural problems for 11-12 year old children decreased. The findings show that the combining of longitudinal and cross-sectional design is useful for studying development from different perspectives.